Performance indicators that discriminate between winning and losing teams in male university rugby sevens teams - Moolman, B. W.; van den Berg, P. H.; Broodryk, R. (International Journal of Performance Analysis in Sport, 2021)
Understanding which performance indicators (PIs) positively affect the success of rugby sevens (RS), teams at university level might assist the coaching staff to optimally prepare for future matches and increase the likelihood of success. This study aimed to determine PIs that discriminate between winning and losing male University-level RS teams. Twenty (n = 20) round-robin matches of the 2018 Varsity sports rugby sevens tournament were analysed. A linear mixed model was used to determine statistically significant differences set at p < 0.05 while effect size was reported according to Cohen`s d. Results revealed that various PIs discriminated between winning and losing RS teams. Therefore, specific identified tactical aspects of RS should be prioritised to optimise performance.